The miraculousness of the Qur’an Composition in the “Al-kursi” verse - Al-Shorafat, Irshaid Ghassab (Journal of Islamic Sciences, 2021)
This paper came under the title: (The Miracle of Qur’anic Systems in the Ayat al-Kursi) to deal with an aspect of the linguistic miracles in the Noble Qur’an, which is the Qur’anic systems in the verse of the Holy Qur’an, and it aimed to search for the structural relationships between the linguistic elements in the ayat al-Kursi to clarify the miraculous aspect of its systems. The analytical structural approach in analyzing sentences and linguistic structures to their primary elements within the verse in order to reach the desired results, the research has concluded that the verse of the Holy Qur'an includes in its systems many aspects of the Qur’anic miracles.
Keywords: miraculousness; composition; Al-kursi; verse